Novel isolates expand the physiological diversity of Prochlorococcus and illuminate its macroevolution - Jamie W. Becker; Shaul Pollak; Jessie W. Berta-Thompson; Kevin W. Becker; Rogier Braakman; Keven D. Dooley; Thomas Hackl; Allison Coe; Aldo Arellano; Kristen N. LeGault; Paul M. Berube; Steven J. Biller; et al. (mBio)
ABSTRACT Prochlorococcus is a diverse picocyanobacterial genus and the most abundant phototroph on Earth. Its photosynthetic diversity divides it into high-light (HL)- or low-light (LL)-adapted groups representing broad phylogenetic grades—each composed of several monophyletic clades. Here, we physiologically characterize four new Prochlorococcus strains isolated from below the deep chlorophyll maximum in the North Pacific Ocean. We combine these physiological properties with genomic analyses to explore the evolution of photosynthetic antennae and discuss potential macroevolutionary implications. The isolates belong to deeply branching low-light-adapted clades that have no other cultivated representatives and display some unusual characteristics. For example, despite its otherwise low-light-adapted physiological characteristics, strain MIT1223 has low chl b2 content similar to high-light-adapted strains. Isolate genomes revealed that each strain contains a unique arsenal of pigment biosynthesis and binding alleles that have been horizontally acquired, contributing to the observed physiological diversity. Comparative genomic analysis of all picocyanobacteria reveals that Pcb, the major pigment carrying protein in Prochlorococcus, greatly increased in copy number and diversity per genome along a branch that coincides with the loss of facultative particle attachment. Collectively, these observations support a recently developed macroevolutionary model, in which niche-constructing radiations allowed ancestral lineages of picocyanobacteria to transition from a particle-attached to planktonic lifestyle and broadly colonize the euphotic zone.IMPORTANCEThe marine cyanobacterium, Prochlorococcus, is among the Earth’s most abundant organisms, and much of its genetic and physiological diversity remains uncharacterized. Although field studies help reveal the scope of diversity, cultured isolates allow us to link genomic potential to physiological processes, illuminate eco-evolutionary feedbacks, and test theories arising from comparative genomics of wild cells. Here, we report the isolation and characterization of novel low-light (LL)-adapted Prochlorococcus strains that fill in multiple evolutionary gaps. These new strains are the first cultivated representatives of the LLVII and LLVIII paraphyletic grades of Prochlorococcus, which are broadly distributed in the lower regions of the ocean euphotic zone. Each of these grades is a unique, highly diverse section of the Prochlorococcus tree that separates distinct ecological groups: the LLVII grade branches between monophyletic clades that have facultatively particle-associated and constitutively planktonic lifestyles, whereas the LLVIII grade lies along the branch that leads to all high-light (HL)-adapted clades. Characterizing strains and genomes from these grades yields insights into the large-scale evolution of Prochlorococcus. The new LLVII and LLVIII strains are adapted to growth at very low irradiance levels and possess unique light-harvesting gene signatures and pigmentation. The LLVII strains represent the most basal Prochlorococcus group with a major expansion in photosynthetic antenna genes. Furthermore, a strain from the LLVIII grade challenges the paradigm that all LL-adapted Prochlorococcus exhibit high ratios of chl b:a2. These findings provide insights into the photophysiological evolution of Prochlorococcus and redefine what it means to be a low- vs high-light-adapted Prochlorococcus cell.